(untitled) (Web of Teachers: Inderscience Research, 2025)
This article examines the role and key strategies of the Central Bank of the Republic of Uzbekistan in combating inflation. It analyzes the impact of inflation on macroeconomic stability, the effectiveness of monetary policy, and the importance of the inflation targeting mechanism. The paper also provides a statistical analysis of inflation indicators for the period 2020–2025, highlighting both positive and negative aspects. Furthermore, based on international experience, the article explores the strengths and weaknesses of Uzbekistan’s model and proposes practical recommendations for improving inflation control.